Do Individual Investors Cause Post-Earnings Announcement Drift? Direct Evidence from Personal Trades - Hirshleifer, David A.; Myers, James N.; Myers, Linda A.; Teoh, Siew Hong (The Accounting Review, 2008)
ABSTRACT: This study tests whether nai¨ve trading by individual investors, or some class of individual investors, causes post-earnings announcement drift (PEAD). Inconsistent with the individual trading hypothesis, individual investor trading fails to subsume any of the power of extreme earnings surprises to predict future abnormal returns. Moreover, individuals are significant net buyers after both negative and positive extreme earnings surprises, consistent with an attention effect, but not with their trades causing PEAD. Finally, we find no indication that trading by individuals explains the concentration of drift at subsequent earnings announcement dates.